2023
DOI: 10.1021/acs.inorgchem.2c03970
|View full text |Cite
|
Sign up to set email alerts
|

Rational Construction of Metal Organic Framework Hybrid Assemblies for Visible Light-Driven CO2 Conversion

Abstract: Photocatalytic reduction of CO 2 to value-added chemicals is known to be a promising approach for CO 2 conversion. The design and preparation of ideal photocatalysts for CO 2 conversion are of pivotal significance for the sustainable development of the whole society. In this work, we integrated two functional organic linkers to prepare a novel metal organic framework (MOF) photocatalyst {[Co(9,10-bis(4-pyridyl)anthracene) 0.5 (bpda)]•4DMF} (Co-MOF). The existence of anthryl and amino groups leads to a wide ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Importantly, highly conjugated BPAN further enhance the charge transfer process. 100 The introduction of other functional groups into MOFs, providing a specific chemical environment near the catalytically active metal site, can show a difference in photocatalytic performance. Some researchers explored sulfided organic ligands, i.e., using thiourea or some sulfur-containing groups (−SH, −SCH 3 ) as a sulfur source for modification to synthesize photocatalysts with a small energy band gap.…”
Section: Designing High-catalytic-activity Mofsmentioning
confidence: 99%
“…Importantly, highly conjugated BPAN further enhance the charge transfer process. 100 The introduction of other functional groups into MOFs, providing a specific chemical environment near the catalytically active metal site, can show a difference in photocatalytic performance. Some researchers explored sulfided organic ligands, i.e., using thiourea or some sulfur-containing groups (−SH, −SCH 3 ) as a sulfur source for modification to synthesize photocatalysts with a small energy band gap.…”
Section: Designing High-catalytic-activity Mofsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are considered promising photocatalysts, which are porous crystalline hybrid materials connected by metal or metal clusters and organic ligands through coordination bonding. MOF materials are very widely used in many aspects, especially for CO 2 capture and conversion, due to the high specific surface area, high porosity, and high density of the catalytic active site. MOF-based photocatalysts have achieved remarkable results in photocatalytic CO 2 reduction in recent years. The catalytic sites of MOFs generally can be from metal unsaturated sites or organic ligands. , In order to enhance the catalytic activities of catalysts, the combination of high-valence metallic ions with variable redox states and highly conjugated organic ligands is an effective strategy. The tetravalent Ti 4+ cation is a class of important metal nodes for MOF photocatalysts. Through the ligand-to-metal charge transfer (LMCT) process, the formation of active intermediate trivalent Ti 3+ is conducive to the progress of the reduction reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] As a consequence, organic dyes in dye-based MOFs are often used as photosensitizers for photocatalytic hydrogen production and CO 2 reduction, which does not make sufficient use of the redox properties of organic dyes, thereby limiting the application of MOFs as photocatalysts. [17][18][19][20][21][22] Taking advantage of the easy modification features of MOFs, introducing the functional groups within MOFs is a promising and effective strategy for tailoring the physical environment of cavities, pores and electronic structures for tar-geted applications. [23][24][25] Recent research has indicated that the functionalization of dye-based ligands can regulate the twisted conjugative junction between the ligands and metal nodes, which enables MOFs to markedly enhance the separation efficiency of photogenerated carriers in MOFs and hamper the futile intramolecular fluorescence quenching, thus enhancing the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…14–16 As a consequence, organic dyes in dye-based MOFs are often used as photosensitizers for photocatalytic hydrogen production and CO 2 reduction, which does not make sufficient use of the redox properties of organic dyes, thereby limiting the application of MOFs as photocatalysts. 17–22…”
Section: Introductionmentioning
confidence: 99%